Hypoxis atlantica (Hypoxidaceae): a rare new species endemic to coastal eastern Brazil - Funez, Luís Adriano; Hassemer, Gustavo; Ferreira, João Paulo Ramos (Phytotaxa, 2016)
This work presents and describes Hypoxis atlantica, a new species only known from two disjunct coastal areas in eastern Brazil. Despite our best efforts to collect this species in other areas, we had to assess its conservation status as data deficient. We include here a complete description, photographs, a distribution map and an updated identification key to the species of Hypoxis in South America.